2019
DOI: 10.1111/eea.12784
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behavior of Myzus persicae on asparagus species susceptible and resistant to Asparagus virus 1

Abstract: Asparagus virus 1 (AV‐1) infects Asparagus officinalis L. (Asparagaceae) in the field worldwide. However, various wild relatives of A. officinalis are resistant to AV‐1. Here we study the behavior of the green peach aphid, Myzus persicae (Sulzer) (Hemiptera: Aphididae), on 19 AV‐1‐resistant wild relatives of A. officinalis. We focus on behavior that is associated with regular cell penetration, relevant for inoculation of AV‐1, and sieve element penetration to check for vector resistance and its potential influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Rhopalosiphum padi biotype R07 (JKI) individuals were reared on 3-to 4-week-old Hordeum vulgare cv. Rubina (Zadoks scale 11-12) in plastic cages with gauze-covered windows in a greenhouse under controlled environmental conditions (day/night regime of 16:8 h, at a temperature of 22 °C-24 °C and a relative humidity of 60%) (Lantos et al 2019). The plants were replaced at 14 day intervals.…”
Section: Aphidsmentioning
confidence: 99%
“…Rhopalosiphum padi biotype R07 (JKI) individuals were reared on 3-to 4-week-old Hordeum vulgare cv. Rubina (Zadoks scale 11-12) in plastic cages with gauze-covered windows in a greenhouse under controlled environmental conditions (day/night regime of 16:8 h, at a temperature of 22 °C-24 °C and a relative humidity of 60%) (Lantos et al 2019). The plants were replaced at 14 day intervals.…”
Section: Aphidsmentioning
confidence: 99%
“…Various studies have indicated that the probing behaviour of aphids on plants could be directly affected by external morphological characteristics and the internal organisational structure of the host plant [36,37]. If the resistance factors are located in the epidermis or mesophyll tissues, aphids exhibit a relatively high frequency of interruption during the probing process, and the probing pathway duration is markedly prolonged [38]. Our results demonstrated that the prying feeding behaviour of T. aurantii differed significantly among the seven tea cultivars.…”
Section: Discussionmentioning
confidence: 61%
“…Until now, there has been no information about the genetic background of the different resistance sources. However, vector resistance was excluded for all these resistance sources by testing the feeding behaviour of the aphid Myzus persicae using an electrical penetration graph (EPG) technique (Lantos et al, 2019).…”
Section: Introductionmentioning
confidence: 99%